Optimalisasi peran satlinmas di kelurahan gilingan kecamatan banjarsari kota surakarta - Wulan Kinasih; Joko Pramono (Universitas Merdeka Malang, 2018)
Indonesia's defense and security system embraces Sishankamrata system. In the case of realizing this sishankamrata, the formation of hansip or community as a component of society which cooperates with TNI and POLRI in realizing security, public order and protection. This study aims to describe the optimization of Satlinmas in Gilingan, Surakarta. The method used in this research is descriptive qualitative. Research data in the form of events obtained from observations and interviews, and supporting documents. Researchers get data by way of observation, interview and documentation. The data were analyzed using interactive analytical models of Miles, Huberman and Saldana. The results showed that the optimization has been implemented in accordance with the role of Satlinmas as stipulated in Permendagri No.84 of 2014 and Surakarta Mayor Regulation No.58 A in 2012. Satlinmas is active in assisting disaster management, both natural and disaster caused by the outbreak of disease outbreak , conducting routine patrols in every area, especially vulnerable areas, assisting community social activities, assisting in the election and defense of the State.DOI: https://doi.org/10.26905/pjiap.v3i1.1922